2015
DOI: 10.2337/dc15-1188
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Glycemic Variability and Risk of Adverse Outcomes: A Systematic Review and Meta-analysis

Abstract: OBJECTIVEGlycemic variability is emerging as a measure of glycemic control, which may be a reliable predictor of complications. This systematic review and meta-analysis evaluates the association between HbA 1c variability and micro-and macrovascular complications and mortality in type 1 and type 2 diabetes. RESEARCH DESIGN AND METHODSMedline and Embase were searched (2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014)(2015) for studies describing associations between HbA 1c variability and advers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
390
2
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 421 publications
(431 citation statements)
references
References 47 publications
(154 reference statements)
24
390
2
3
Order By: Relevance
“…In addition, respondents were not always able to respond accurately. Corroborating the literature (4,(24)(25) , the present study presented a positive statistical relationship between inadequate glycemic control and the occurrence of DM-related complications, although this variable was not maintained in the final model, perhaps because it was closely linked to the duration of diabetes.…”
Section: Discussionsupporting
confidence: 77%
“…In addition, respondents were not always able to respond accurately. Corroborating the literature (4,(24)(25) , the present study presented a positive statistical relationship between inadequate glycemic control and the occurrence of DM-related complications, although this variable was not maintained in the final model, perhaps because it was closely linked to the duration of diabetes.…”
Section: Discussionsupporting
confidence: 77%
“…This is the first analysis to consider the relationship between clinically significant variations in glycaemic control and mortality in older people. While previous studies have shown that variability in HbA1c increases hazard for diabetes complications and mortality, 11,18,19 these studies were not specific to older people and used variability estimations based on standard deviation(SD) of the mean HbA1c. Whereas our variability metric was weighted for clinically significant change in HbA1c (≥ 0·5%,5·5 mmol/mol) and we also considered the frequency and direction of variation to provide more granularity in our interpretation.…”
Section: Discussionmentioning
confidence: 99%
“…41,48,51 During recent years, the effect of long-term glucose variability, as assessed by the intraindividual variability of HbA1c values across visits, on retinopathy, nephropathy, and cardiovascular complications has also been documented. 52 However, HbA1c measurement does not give any information about individual daily glucose fluctuations (short-term fluctuations or acute hyperglycemia). In patients with marked fluctuations in glucose concentrations who are exposed to the risk of both hyperglycemia and hypoglycemia, HbA1c levels may still indicate adequate metabolic control.…”
Section: Chronic Versus Acute Hyperglycemia In the Pathogenesis Of Vamentioning
confidence: 99%